Local and Systemic STAT3 and p65 NF-KappaB Expression as Progression Markers and Functional Targets for Patients With Cervical Cancer - Rossetti, Renata A. M.; da Silva-Junior, Ildefonso A.; Rodríguez, Gretel R.; Alvarez, Karla L. F.; Stone, Simone C.; Cipelli, Marcella; Silveira, Caio R. F.; Beldi, Mariana Carmezim; Mota, Giana R.; Margarido, Paulo F. R.; Baracat, Edmund C.; Uno, Miyuki; et al. (Frontiers in Oncology, 2020)
Cervical cancer, which main etiologic factor is Human Papillomavirus (HPV) infection, continues to be a burden for public health systems in developing countries. Our laboratory has been working with the hypothesis that signals generated in the tumor microenvironment can modulate local and systemic immune responses. In this context, it would be reasonable to think that tumors create pro-tumoral bias in immune cells, even before they are recruited to the tumor microenvironment. To understand if and how signaling started in the tumor microenvironment can influence cells within the tumor and systemically, we investigated the expression of key proteins in signaling pathways important for cell proliferation, viability, immune responses and tolerance. Besides, we used detection of specific phosphorylated residues, which are indicative of activation for Akt, CREB, p65 NFkB and STAT3. Our findings included the observation of a significant STAT3 expression increase and p65 NFkB decrease in circulating leukocytes in correlation with lesion grade. In light of those observations, we started investigating the result of the inhibition of STAT3 in a tumor experimental model. STAT3 inhibition impaired tumor growth, increased anti-tumor T cell responses and decreased the accumulation of myeloid cells in the spleen. The concomitant inhibition of NFkB partially reversed these effects. This study indicates that STAT3 and NFkB are involved in immunomodulatory tumor effects and STAT3 inhibition could be considered as therapy for patients with cervical cancer.